viết dưới dạng tích
(3x+1)2-(x+1)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=\left(x+4\right)^2\\ b,=\left(x-6\right)^2\\ c,=-\left(4x^2-4x+1\right)=-\left(2x-1\right)^2\\ d,=\left(x-1\right)^3\)
Ta có x 3 + 3 x 2 + 3 x + 1 = x 3 + 3 x 2 . 1 + 3 x . 1 2 + 1 3 = ( x + 1 ) 3 .
\(x^2+3x+2=x^2+x+2x+2=x\left(x+1\right)+2\left(x+1\right)=\left(x+1\right)\left(x+2\right)\)
(x - 3) ( x2 + 3x + 9 )
= ( x - 3 ).( x2 + x.3 + 32 )
= x3 - 33
= x3 - 27
(3x+1)\(^2\)-(x+1)\(^2\) =(3x+1+x+1)(3x+1-x-1) = 2x(4x+2) =4x(2x+1)